Corrosion inhibition of zinc in hydrochloric acid solution using Ampicillin - saleh, Khulood; Khalil, Khalil (Iraqi Journal of Science, 2023)
The corrosion behavior of Zn in 0.1 M HCl solution containing various concentration of Ampicillin range (2 x 10-4 – 1x10-3) M was investigated. The corrosion rates were measured by using weight loss measurement and polarization curve, The results of polarization method obtained showed that the rate of corrosion of zinc increased with increasing the temperature from 293K to 323K and the values of inhibition efficiency of ampicillin increased with increasing the temperature and AMP concentrations, the results showed that AMP caused to protection efficiency reached to 88.8% when (1x10-3) M AMP concentration was used in 323K. The coverage (θ) of metal surface by AMP could be obtained from the rate of corrosion in the presence and absence of AMP in the acid solution. A linear relationship was found to exist between the value of (C/θ) and the corresponding AMP concentration (C) indicating that the inhibition action to occur via adsorption mechanism. Changes in the free energy, enthalpy and entropy associated with AMP adsorption have been determined. Apparent energies of activation have been calculated for the corrosion process of zinc in the acid from corrosion rates and Arrhenius Plots.